PERLINDUNGAN ANAK DI SEKOLAH: MENYIKAPI PELANGGARAN HAM DALAM BENTUK VERBAL BULLYING BERBASIS NAMA ORANG TUA - Ahmad Kristanto; Muhammad Naufal Fikri (Kampus Akademik Publiser, 2023)
Education is crucial for a nation because prosperous nations will certainly prioritize education, as is the case in Indonesia. With the improvement of education, issues such as violence in school environments are bound to continue to arise. Therefore, there is a need for protection by teachers, school principals, and parents. This article investigates the issue of child protection in the school environment with a focus on verbal bullying that involves the use of parents' names as a form of intimidation. This study seeks to understand the psychological, social, and academic impact of such behavior on students. Furthermore, this article explores the steps taken by schools and authorities to prevent and address these bullying incidents with the goal of creating a safe and supportive learning environment for all children.